The Influence of Herbicides to Marine Organisms Aliivibrio fischeri and Artemia salina - Radek Vurm (MDPI AG, 2021)
The aim of this work was to determine the toxic effect of the most used herbicides on marine organisms, the bacterium Aliivibrio fischeri, and the crustacean Artemia salina. The effect of these substances was evaluated using a luminescent bacterial test and an ecotoxicity test. The results showed that half maximal inhibitory concentration for A. fischeri is as follows: 15minIC50 (Roundup® Classic Pro) = 236 μg·L−1, 15minIC50 (Kaput® Premium) = 2475 μg·L−1, 15minIC50 (Banvel® 480 S) = 2637 μg·L−1, 15minIC50 (Lontrel 300) = 7596 μg·L−1, 15minIC50 (Finalsan®) = 64 μg·L−1, 15minIC50 (glyphosate) = 7934 μg·L−1, 15minIC50 (dicamba) = 15,937 μg·L−1, 15minIC50 (clopyralid) = 10,417 μg·L−1, 15minIC50 (nonanoic acid) = 16,040 μg·L−1. Median lethal concentrations for A. salina were determined as follows: LC50 (Roundup® Classic Pro) = 18 μg·L−1, LC50 (Kaput® Premium) = 19 μg·L−1, LC50 (Banvel® 480 S) = 2519 μg·L−1, LC50 (Lontrel 300) = 1796 μg·L−1, LC50 (Finalsan®) = 100 μg·L−1, LC50 (glyphosate) = 811 μg·L−1, LC50 (dicamba) = 3705 μg·L−1, LC50 (clopyralid) = 2800 μg·L−1, LC50 (nonanoic acid) = 7493 μg·L−1. These findings indicate the need to monitor the herbicides used for all environmental compartments.